Behavior and evolution (Cambridge, New York, 1994)
The book illustrates how the profound changes in our understanding of evolution have influenced behavioural research. Its chapters cover studies of how behaviour itself has evolved, dealing with topicss such as comparative studies, the genetics of behaviour, speciation and the evolution of sociality and of intelligence. They also deal with the adaptiveness which this evolution has brought about, with mating and fighting strategies, and with theories of kindship and altruism
Keywords: animal behavior,behavior evolution